2013
DOI: 10.1111/ijfs.12211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave and ultrasound pretreatments on enzymolysis of milk protein concentrate with different enzymes

Abstract: Milk protein concentrate was pretreated either by microwave irradiation or by ultrasound before initiation of 3-h enzymatic hydrolysis. The duration of pretreatment ranged from 1 to 8 min at a power level of 800 W, with the control not being subjected to any pretreatment, and five enzymes (Alcalase, Trypsin, Neutrase, Alkaline Protease and Flavourzyme) were employed. The effects of microwave and ultrasound pretreatments on the kinetics and degree of hydrolysis, protein solubility, bitterness and angiotensincon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 35 publications
(45 reference statements)
6
40
1
Order By: Relevance
“…It has been reported that sonication could favor the enlargement of soluble protein aggregates from insoluble precipitates [58]. Higher solubility after sonication is also reported some other researchers [9,27,53,54,59]. It can be concluded that rapeseed protein pretreatment by ultrasound is an attractive approach improvement of functional characteristics.…”
Section: Effect Of Ultrasound Pretreatment On Solubility Of Rapeseed mentioning
confidence: 58%
See 3 more Smart Citations
“…It has been reported that sonication could favor the enlargement of soluble protein aggregates from insoluble precipitates [58]. Higher solubility after sonication is also reported some other researchers [9,27,53,54,59]. It can be concluded that rapeseed protein pretreatment by ultrasound is an attractive approach improvement of functional characteristics.…”
Section: Effect Of Ultrasound Pretreatment On Solubility Of Rapeseed mentioning
confidence: 58%
“…The solutions were incubated and stirred continuously using magnetic stirrer for 30 min in a thermostat water bath at 40 ∘ C to ensure complete dissolution and then subjected to cool to room temperature. After that, the solutions were given treatment using probe-type sonicator ( Figure 1) (GA98-IID, Shanghai Biotechnology Co., Wuxi, China) at 20 kHz with a 1.5 cm flat tip probe (diameter of 2 cm) which was immersed into the rapeseed protein solution for different irradiation time (3,6,9,12,15, and 18 min) and at different powers (200, 400, 600, 800, 1000, and 1200 watts).…”
Section: Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the potential of heat pretreatment to improve enzymatic hydrolysis of EWPs has been explored widely in the last decade [24], such method leads to destruction of some functional properties of egg white, such as gelling and foaming, which are often desirable for food manufacture [13]. Ultrasound pretreatment has also been used to improve the hydrolysis of several proteins [25] and in turn improve the production of angiotensin-converting enzyme (ACE) inhibitory peptides, by causing unfolding of protein chains and thus release possible peptides that are responsible for ACE-inhibitory activity [26]. Despite the promising effects of sonication alone or in combination with heat or pressure on a laboratory scale, there is limited information on the hydrolysis of EWPs from different ultrasound treatments and proteolytic enzyme systems.…”
Section: Introductionmentioning
confidence: 99%